The influence of instructional leadership and work commitment on teacher performance - Nellitawati, Nellitawati; Ganefri, Ganefri; Rusdinal, Rusdinal; Hardianto, Hardianto; Ali Setiawan, Muhammad Nurhisyam; Ginanjar, Singgih; Arwildayanto, Arwildayanto (Jurnal Cakrawala Pendidikan, 2024)
This research explores the influence of the principal’s instructional leadership and teacher work commitment on teacher performance in Vocational High Schools in Padang City. This research aims to measure how much the two variables contribute to the effectiveness of teacher performance. Using descriptive quantitative methods, this research involved 133 teachers as samples. Regression analysis is used to analyze the relationship between variables. The research showed that the principal’s instructional leadership contributed 7.8% to improving teacher performance, while work commitment contributed 22.5%. When these two variables were combined, they explained 23.1% of the variability in teacher performance. This research underlines the importance of effective instructional leadership and high work commitment in improving teacher performance. In addition, this research recommends that other factors that influence teacher performance, such as social support and school culture, be further explored in future research. In conclusion, these findings provide important insights for developing educational policies that support the role of principals as instructional leaders and motivate teachers’ work commitment, which can ultimately improve overall educational outcomes.